Semantic Analysis of the Term Fitna in the Qur'an - Muhammad Hanif al Hakim; Azhar Alam (Institut Agama Islam Negeri (IAIN) Curup, 2019)
Some Muslim groups often quote the Qur'anic verse Chapter Al-Baqarah 191 which shows the meaning of al-fitnatu asyadd min al-qatl. Based on that verse, they encourage every member of the Muslim community not to cast slander to other Muslims because slander is worse than killing. The meaning of the term slander is still ambiguous and this article tries to explore its nuances. By using a qualitative approach and semantic analysis method, this study tries to describe various interpretations of slander from several prominent literary sources. This study aims to uncover the bulk of meanings of the word fitna as well to balance and to improve the narrow understanding of slander. This study found that the scope of meaning for the word fitna, includes words such as accusations, calamities, conflicts and disputes, which all have one purpose, i.e. efforts to find out which Muslims are good and which Muslims are bad. Fitna unexpectedly can befall us in various forms. Just like education tests, examinees or Muslims who are facing defamation must know how to overcome them.